Circuit board and semiconductor device

By controlling the distribution of Ti and Sn or In in the bonding layer of the ceramic copper circuit substrate, a rich and poor Ti zone is formed, and the problem of reducing the melting point of the copper plate caused by Ag, Sn and In diffusion is solved, and an efficient bonding process is achieved. Mass production performance improves the thermal stability and bonding strength of the joint.

CN119285367APending Publication Date: 2025-01-10SPECIAL CERAMIC MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411392578.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2020-07-27
Filing Date
2021-07-19
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

During the bonding process, the existing ceramic copper circuit substrates have a lower melting point due to the diffusion of Ag, Sn and In, which affects the deformation and temperature cycle test characteristics of the joint. The vacuum bonding process is low, making it difficult to achieve mass production.

Method used

By controlling the distribution of Ti and Sn or In in the bonding layer, a rich and poor Ti regions are formed, and the distribution ratio of Ti and Sn is determined by SEM-EDX and electron reflection image analysis, the diffusion of Sn or In to the copper plate is suppressed, and the The bonding process is optimized using high-temperature speed bonding and DSC curve.

Benefits of technology

The diffusion of Sn or In to the copper plate is effectively suppressed, the thermal stability and mass production of the joint are improved, the warping amount of the joint and the deformation of the copper plate are reduced, and the bonding strength is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285367A_ABST
    Figure CN119285367A_ABST
Patent Text Reader

Abstract

A bonded body according to an embodiment is provided with a ceramic substrate, a copper plate, and a bonding layer disposed on at least one surface of the ceramic substrate for bonding the ceramic substrate and the copper plate, and is characterized in that: the bonding layer contains Cu, Ti, and one or two first elements selected from among Sn and In; the bonding layer includes a Ti-rich region in which the ratio (MTi / ME1) of the mass MTi of Ti to the mass ME1 of the first element is 0.5 or more, and a Ti-poor region in which the ratio (MTi / ME1) is 0.1 or less.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the application with application number "202180059558.5", application date July 19, 2021, and invention name "Joint body, circuit substrate, semiconductor device and method for manufacturing joint body". Technical Field

[0002] The embodiments described below relate to a bonded body, a circuit board, a semiconductor device, and a method for manufacturing a bonded body. Background Art

[0003] The joint body of a ceramic substrate and a copper plate is used as a circuit substrate for mounting semiconductor elements and the like. International Publication No. 2018 / 021472 (Patent Document 1) discloses a ceramic copper circuit substrate in which a ceramic substrate and a copper plate are joined. In Patent Document 1, a brazing material containing Ag, Cu, Ti, etc. is used in the joining layer. In Patent Document 1, the bonding layer is 1×10 - 3 Heat bonding is performed at a pressure of less than 100 Pa.

[0004] Such 1×10 -3 The pressure below Pa is called vacuum. The bonding method using Ti is called active metal bonding. Ti is easily nitrided or oxidized because it is an active metal. In the active metal bonding method, bonding is performed in a vacuum to prevent Ti from nitriding and oxidizing before bonding. To bond in a vacuum, the inside of the bonding device must be vacuumed. After the vacuum is formed, the temperature is gradually increased, so only batch processing can be used in the heating bonding process. Each batch of the heating bonding process includes four steps: vacuuming, heating, bonding, and cooling. Each batch takes more than 24 hours. Therefore, it cannot be said that mass productivity is good.

[0005] On the other hand, in International Publication No. 2018 / 199060 (Patent Document 2), a heating bonding process is disclosed using a continuous furnace. In the embodiment of Patent Document 2, bonding is performed at a furnace length of 3m and a conveying speed of 10cm / minute. Including the holding time in the middle, the heating bonding can be performed in about 2 hours.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: International Publication No. 2018 / 021472

[0009] Patent Document 2: International Publication No. 2018 / 199060 Summary of the invention

[0010] Problem that the invention aims to solve

[0011] In Patent Documents 1 and 2, more than 40 wt% of Ag is contained as a bonding brazing material. Sn and In are also used in the bonding brazing material. Ag is an element that easily diffuses into the copper plate. As Ag diffuses, Sn and In also diffuse into the copper plate. If Sn or In diffuses into the copper plate, the melting point of the copper plate decreases. If the melting point of the copper plate decreases, it becomes a cause of the deformation during bonding and the degradation of the temperature cycling test (TCT) characteristics. It is known that in order to prevent Sn or In from diffusing into the copper plate, it is effective to control the distribution of Ti and the distribution of Sn or In in the bonding layer.

[0012] The present invention has been made to address such problems, and provides a bonded body in which the distribution of Ti and Sn or In in a bonding layer is controlled.

[0013] Means used to solve problems

[0014] The joint body according to the embodiment is characterized in that it comprises a ceramic substrate, a copper plate, and a joint layer disposed on at least one surface of the ceramic substrate for joining the ceramic substrate and the copper plate, wherein the joint layer contains Cu, Ti, and a first element selected from one or two of Sn and In, and the mass M of the Ti is Ti Relative to the mass M of the first element E1 The ratio (M Ti / M E1 ) is 0.5 or more and the ratio (M Ti / M E1 ) is a titanium-poor area below 0.1. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 It is a diagram showing an example of a joined body according to an embodiment.

[0016] Figure 2 It is a diagram showing an example of a bonding layer of a bonded body according to an embodiment.

[0017] Figure 3 It is a diagram showing an example of a circuit board according to the embodiment.

[0018] Figure 4 FIG. 1 is a diagram showing an example of a semiconductor device according to an embodiment.

[0019] Figure 5 This is a DSC curve of the temperature increase step of the bonding brazing material of Example 1 (500 to 600° C.).

[0020] Figure 6 This is a DSC curve of the temperature increase step of the bonding brazing material of Example 1 (700 to 900° C.). DETAILED DESCRIPTION

[0021] The joint body according to the embodiment is characterized in that it comprises a ceramic substrate, a copper plate, and a joint layer disposed on at least one surface of the ceramic substrate for joining the ceramic substrate and the copper plate, wherein the joint layer contains Cu, Ti, and a first element selected from one or two of Sn and In, and the mass M of the Ti is Ti Relative to the mass M of the first element E1 The ratio (M Ti / M E1 ) is 0.5 or more and the ratio (M Ti / M E1 ) is a titanium-poor area below 0.1.

[0022] Figure 1 It is a schematic diagram which shows an example of a joint body. Figure 1 In the figure, 1 is a bonded body, 2 is a ceramic substrate, 3 is a copper plate, and 4 is a bonding layer. Figure 1 FIG. 1 shows a bonded body 1 in which copper plates 3 are disposed on both surfaces of a ceramic substrate 2 via bonding layers 4. Figure 1 In the example, the vertical and horizontal dimensions of the ceramic substrate 2 and the copper plate 3 are the same. The joint body involved in the embodiment is not limited to such a form, and may have a structure in which the copper plate 3 is provided only on one side of the ceramic substrate 2. In addition, the vertical and horizontal dimensions of the ceramic substrate 2 and the copper plate 3 may be different from each other.

[0023] As the ceramic substrate 2, a silicon nitride substrate, an aluminum nitride substrate, an aluminum oxide substrate, an Alusil high silicon heat-resistant aluminum alloy substrate, etc. can be cited. The thickness of the ceramic substrate 2 is preferably 0.1 mm or more and 1 mm or less. If the substrate thickness is less than 0.1 mm, there is a possibility that the strength of the ceramic substrate 2 decreases. In addition, if the substrate thickness is greater than 1 mm, the ceramic substrate becomes a thermal resistor, and there is a possibility that the heat dissipation of the joint body is reduced.

[0024] The three-point bending strength of the silicon nitride substrate is preferably 600 MPa or more. In addition, the thermal conductivity is preferably 80 W / mTK or more. By increasing the strength of the silicon nitride substrate, the substrate thickness can be reduced. Therefore, the three-point bending strength of the silicon nitride substrate is preferably 600 MPa or more, more preferably 700 MPa or more. The substrate thickness of the silicon nitride substrate can be reduced to less than 0.40 mm, and further reduced to less than 0.30 mm.

[0025] The three-point bending strength of the aluminum nitride substrate is in the range of 300 to 450 MPa. On the other hand, the thermal conductivity of the aluminum nitride substrate is 160 W / mTK or more. Since the strength of the aluminum nitride substrate is low, the substrate thickness is preferably 0.60 mm or more.

[0026] The three-point bending strength of an alumina substrate is in the range of 300 to 450 MPa, but the alumina substrate is inexpensive. In addition, the three-point bending strength of an alusil high-silicon heat-resistant aluminum alloy substrate is as high as about 550 MPa, but the thermal conductivity is in the range of 30 to 50 W / m·K.

[0027] The ceramic substrate 2 is preferably any one of a silicon nitride substrate and an aluminum nitride substrate. The silicon nitride substrate and the aluminum nitride substrate are nitride ceramic substrates. Nitride ceramics react with an active metal brazing material containing Ti to form titanium nitride. In addition, oxide ceramics react with an active metal brazing material containing Ti to form titanium oxide.

[0028] An oxygen-free copper plate or a copper alloy plate can be used as the copper plate 3. The copper plate 3 is preferably oxygen-free copper. Regarding oxygen-free copper, as shown in JIS-H-3100 (ISO1337, etc.), the copper purity is 99.96 wt% or more.

[0029] The bonding layer contains Cu, Ti, and one or two first elements selected from Sn and In.

[0030] Cu (copper) is an element that becomes the base material of the bonding layer. Even if Cu diffuses into the copper plate, it will not deteriorate the copper plate. Ti (titanium) is an effective element for forming a strong bond by reacting with the ceramic substrate. Sn (tin) or In (indium) is an effective element for lowering the melting point of the bonding brazing material that forms the bonding layer. As described later, in order to obtain the bonding layer as the target, it is effective to increase the heating rate. For this reason, it is necessary to contain Sn or In.

[0031] The bonding layer is characterized by having a Ti-rich region and a Ti-poor region. In the Ti-rich region, the mass of Ti M Ti Relative to the mass of the first element M E1 The ratio (M Ti / M E1 ) is greater than 0.5. In the Ti-poor region, the mass of Ti M Ti Relative to the mass of the first element M E1 The ratio (M Ti / M E1 ) is less than 0.1. The Ti content in the Ti-rich region is greater than the Ti content in the Ti-poor region.

[0032] Figure 2 It is a schematic diagram showing an example of a bonding layer. Figure 2 In the figure, 2 is a ceramic substrate, 3 is a copper plate, 4 is a bonding layer, 4a is a Ti cohesive layer, 5 is a Ti-rich region, 5a is a Ti-medium region, 6 is a Ti-poor region, and 7 is a diffusion region. Figure 2 In the bonding layer 4 in FIG. 1 , the regions with dots are the Ti-rich region 5 and the Ti-medium region 5a. The dot density of the Ti-rich region 5 is higher than that of the Ti-medium region 5a.

[0033] In the analysis of the mass ratio of Ti and the first element, a scanning electron microscope-X-ray energy dispersive spectrum (Scanning Electron Microscope-Energy Dispersive X-ray spectroscopy, SEM-EDX) is used. Below, an example in which the first element is Sn is described. The cross section of the joint body 1 is used as the measurement area. The cross section of the joint body 1 is a cross section parallel to the direction perpendicular to the surface of the ceramic substrate 2. In addition, when analyzing the mass ratio of Ti and the first element, the measurement area is set only to the joint layer 4. That is, the ceramic substrate 2 and the copper plate 3 are not included in the measurement area.

[0034] As SEM, JSM-IT100 manufactured by JEOL or a device with equivalent performance is used. As EDX, EX-9440IT4L11 manufactured by JEOL or a device with equivalent performance is used. First, the measurement area of ​​20μm×10μm is analyzed by EDX. The 20μm in the measurement area is the length in the direction parallel to the surface of the ceramic substrate 2. The 10μm in the measurement area is the length in the direction perpendicular to the surface of the ceramic substrate 2. The measurement area is defined as 20μm×10μm because this is a range suitable for investigating the distribution of the bonding layer components. When the thickness of the bonding layer 4 is less than 10μm, the measurement area is set to "10μm×the thickness of the bonding layer 4".

[0035] Ti-rich region 5 is mass ratio (M Ti / M E1 ) is greater than 0.5. The Ti-poor region 6 is a region with a mass ratio (M Ti / M E1 ) is less than 0.1. In the active metal bonding method using Ti, the ceramic substrate 2 is bonded by the reaction of the ceramic substrate 2 with the Ti in the brazing material. Therefore, a Ti coagulation layer is formed on the surface of the ceramic substrate 2. For example, if the ceramic substrate 2 is a nitride ceramic, the Ti coagulation layer is a titanium nitride (TiN) layer. If the ceramic substrate 2 is an oxide ceramic substrate, the Ti coagulation layer is a titanium oxide (TiO2) layer.

[0036] The mass ratio in the Ti-rich region (M Ti / M E1 ) is not particularly limited, but is preferably 1.2 or less. Ti / M E1 ) exceeds 1.2, either too much Ti or too little Sn (or In) may occur. In this case, when the heating rate is increased, the bonding property may be reduced. Therefore, the mass ratio (M) in the Ti-rich region is Ti / ME1 ) is preferably greater than or equal to 0.5 and less than or equal to 1.2.

[0037] The Ti-rich region 5 can suppress excessive diffusion of Sn (or In) into the copper plate. That is, Ti has a trapping effect of retaining Sn in the bonding layer 4.

[0038] The mass ratio (M Ti / M E1 ) is less than 0.1. By having both the Ti-rich region 5 and the Ti-poor region 6 in the bonding layer 4, it is possible to achieve both the effect of suppressing the diffusion of Sn into the copper plate and the effect of improving bonding. The mass ratio (M Ti / M E1 ) includes zero. The Ti amount of zero means that it is below the detection limit.

[0039] A TiSn alloy exists in a part of the Ti-rich region 5. A TiSn alloy may also exist in a part of the Ti-poor region 6. The main component of the Ti coagulation layer 4 is titanium nitride or titanium oxide as described later. The Ti-rich region and the Ti-poor region can be distinguished from the Ti coagulation layer formed on the surface of the ceramic substrate 2. In addition, in the measurement area, a mass ratio (M Ti / M E1 ) is in the range of 0.2 or more and 0.4 or less. Ti / M E1 ) is greater than 0.2 and less than 0.4 is called the Ti medium area. In addition, the TiSn alloy in the Ti-rich area 5 and the Ti-poor area 6 may also contain intermetallic compounds. Examples of intermetallic compounds include Sn3Ti5 and Sn5Ti6. In addition, it is preferred that more than 50% of the TiSn alloy is Sn3Ti5 or Sn5Ti6. The presence of Sn3Ti5 or Sn5Ti6 indicates that it is suitable for the bonding reaction.

[0040] In the Ti-rich region 5, the mass of Cu M Cu Relative to the mass of the first element M E1 The ratio (M Cu / M E1 ) is preferably 0.05 or more and 0.4 or less. In the Ti-poor region 6, the mass ratio (M Cu / M E1 ) is preferably 3 or more and 10 or less. The presence of Cu in the Ti-rich region 5 and the Ti-poor region 6 can reduce the melting point of the bonding layer 4. If the melting point of the bonding layer 4 is reduced, the bonding property can be improved even if the heating time is accelerated as described later. Intermetallic compounds such as CuSn, CuIn, CuSnTi, and CuInTi may also exist in the Ti-rich region 5 and the Ti-poor region 6.

[0041] The above-mentioned Ti-rich region is mainly composed of a TiSn alloy with a large amount of Sn with a large atomic number. When observing the cross-section of the bonding layer through the reflected electron image of the SEM, the element with a large atomic number looks whitish compared to the element with a small atomic number. Therefore, when observing the electron reflection image of the SEM with high contrast, the TiSn alloy looks whitish. The amount of TiSn alloy in the Ti-rich region is sufficiently greater than the amount of TiSn alloy in the Ti-poor region. That is, in the bonding layer observed by the electron reflection image, the whitish area can be regarded as a Ti-rich region. The area observed as whitish at high contrast preferably exists in an area ratio of more than 10% in a unit measurement area of ​​20μm×10μm. In addition, by observing the reflected electron image, the area ratio of the Ti-rich region can be obtained. In addition, the upper limit of the area that looks whitish is preferably 90% in terms of area ratio. Both the Ti-rich region 5 and the Ti-poor region 6 need to exist in the measurement area 20μm×10μm. In addition, by combining with the above-mentioned SEM-EDX, the area ratio of the Ti-rich region can also be obtained. Furthermore, regarding the contrast of the reflected electron image of the SEM, the elements with larger atomic numbers appear whiter. Ti / M E1 ) is greater than 0.5 and less than 1.2, it is easy to distinguish the Ti-rich area and the Ti-poor area by contrast. In addition, the contrast of the electron reflection image of the SEM varies depending on the device. Therefore, the method of investigating based on the shade of white is effective. Therefore, the method using the electron reflection image can be used as a simplified version of the method using EDX.

[0042] The area ratio of the Ti-rich zone is preferably greater than 10% and less than 90%, and more preferably within the range of greater than 20% and less than 60%. In addition, in addition to the Ti-rich zone, there is also a Ti-poor zone or a Ti-medium zone in the bonding layer. In addition, the area ratio of the Ti-poor zone is preferably within the range of greater than 10% and less than 50%. In addition, in the measurement area 20μm×10μm, there may also be areas other than the Ti-rich zone, the Ti-medium zone and the Ti-poor zone. For example, when using a Cu-Sn-Ti-C based brazing material, an area where Sn is not present is sometimes formed. The area where Sn is not present does not correspond to any of the Ti-rich zone, the Ti-medium zone and the Ti-poor zone. Therefore, as long as the Ti-rich zone, the Ti-medium zone and the Ti-poor zone meet the above ranges, there may also be areas where Sn or In is not present.

[0043] When the cross section of the bonding layer is divided into two equal parts, the mass ratio (M Ti / M E1 ) is greater than the mass ratio (M Ti / M E1 For example, when performing surface analysis on the cross section of the bonding layer, the mass M of Ti is Ti Mass M relative to SnSn The ratio (M Ti / M Sn ) is preferably less than 1. In addition, when the cross section of the bonding layer is analyzed, the mass M of Ti is Ti Mass M relative to In In The ratio (M Ti / M In ) is preferably less than 1.

[0044] The so-called dividing the cross section of the bonding layer into two equal parts, upper and lower, means drawing a straight line perpendicular to the surface of the ceramic substrate from the bonding interface between the ceramic substrate and the bonding layer to the bonding interface between the bonding layer and the copper plate, and drawing a straight line parallel to the surface of the ceramic substrate from the center of the straight line. The bonding interface between the ceramic substrate 2 and the bonding layer 4 is the bonding interface between the ceramic substrate 2 and the Ti coagulation layer 4a. As long as the ceramic substrate 2 is a nitride-based ceramic substrate, the Ti coagulation layer is a titanium nitride (TiN) layer. The bonding interface between the bonding layer 4 and the copper plate 3 is the farthest point (the farthest point from the ceramic substrate 2) where the components of the bonding layer are connected and in contact with the copper plate 3. Since the components of the bonding layer 4 contain Ti and the first element, the bonding interface between the bonding layer 4 and the copper plate 3 can be determined based on the diffusion state of these elements. Furthermore, the Ti coagulation layer, i.e., titanium nitride, may also contain an atomic ratio of titanium to nitrogen other than 1:1.

[0045] When the ceramic substrate is an oxide-based ceramic, the Ti coagulation layer is titanium oxide. Titanium oxide as the Ti coagulation layer can exist in various forms such as TiO2, TiO, Ti2O3, etc. When an oxide-based ceramic substrate is used, the above-mentioned titanium nitride is replaced with titanium oxide to determine the bonding interface.

[0046] When the cross section of the bonding layer is divided into two equal parts, the mass ratio (M Ti / M E1 ) is greater than the mass ratio (M Ti / M E1 ), indicating that the amount of Ti in the copper plate side region of the bonding layer is small or the amount of the first element is large. In addition, when the cross section of the bonding layer is analyzed, the mass ratio (M Ti / M Sn ) is less than 1, indicating that the amount of Sn in the bonding layer is greater than the amount of Ti. Similarly, when the cross section of the bonding layer is analyzed, the mass ratio (M Ti / M In ) is lower than 1, indicating that the amount of In in the bonding layer is greater than the amount of Ti.

[0047] By controlling the distribution of Ti and the first element, the diffusion of the first element into the copper plate can be suppressed. This can suppress the melting point of the copper plate from decreasing and suppress the deformation of the copper plate during bonding. As a result, the warping of the bonded body during bonding can be reduced.

[0048] The height of the diffusion region where the diffusion amount of Sn or In into the copper plate is 1wt% or more from the interface between the bonding layer and the copper plate is preferably 100μm or less. The height of the diffusion region is equivalent to the distance from the interface between the bonding layer and the copper plate to the boundary between the region where the diffusion amount of Sn or In in the copper plate is 1wt% or more and the region where the diffusion amount of Sn or In is less than 1wt%. More preferably, the height of the diffusion region is 50μm or less.

[0049] The melting point of CuSn alloy decreases as the amount of Sn increases. If Sn diffuses into the copper plate, a CuSn alloy is formed in the copper plate. If the amount of Sn diffused is large, the amount of Sn in the CuSn alloy increases. As a result, if the melting point of the copper plate decreases, deformation of the copper plate is likely to occur during the joining process and TCT test. Generally speaking, the melting point of copper is 1085°C. If the amount of Sn in the CuSn alloy reaches more than 50wt%, the melting point of the CuSn alloy reaches 100-300°C. If the amount of Sn diffused into the copper plate is small, there is no effect, but if the amount of Sn diffused increases, an effect occurs. Therefore, the height of the diffusion region 7 in which the amount of Sn or In diffused into the copper plate 3 is more than 1wt% is preferably less than 100μm, and more preferably less than 50μm.

[0050] When an oxygen-free copper plate is used as a copper plate, the content of Sn or In in the copper plate can be regarded as the diffusion amount of Sn or In. As a copper plate, a copper alloy plate containing Sn or In can also be used. In the copper alloy plate, Sn or In is uniformly dispersed. Therefore, by measuring the content of Sn or In in the surface side of the copper plate (the so-called surface of the copper plate) and the content in the back side of the copper plate (diffusion area 7), the diffusion amount can be calculated by subtracting the content in the surface side from the content in the back side. The back side of the copper plate is the surface bonded to the ceramic substrate. The surface is the surface on the opposite side of the back side and does not contact the bonding layer. Even when a copper alloy plate is used, the melting point of the copper alloy plate is reduced due to the diffusion of Sn or In, so it is preferred to suppress the diffusion of Sn or In. Furthermore, the melting point of the copper alloy plate containing Sn or In is lower than the melting point of the oxygen-free copper plate not containing Sn or In. Therefore, it is preferred that the copper plate is an oxygen-free copper plate.

[0051] The thickness of the copper plate is preferably 0.3 mm or more. If the copper plate 3 is thick, the current carrying capacity and heat dissipation can be improved. Therefore, the thickness of the copper plate 3 is preferably 0.3 mm or more, and more preferably 0.6 mm or more. The joint body involved in the embodiment can reduce the diffusion area 7 where Sn or In diffuses into the copper plate, so even if the copper plate is thickened, deformation can be suppressed.

[0052] The upper limit of the thickness of the copper plate 3 is not particularly limited, but is preferably less than 3 mm, more preferably less than 2 mm. Even if the thickness of the copper plate exceeds 3 mm, it can be joined. On the other hand, if the copper plate is too thick, the difficulty of etching becomes high. Etching is performed in order to give the copper plate a pattern shape. Therefore, the thickness of the copper plate is preferably more than 0.3 mm and less than 3 mm.

[0053] The bonding layer 4 may contain elements other than Cu, Ti, Sn, and In. Examples of elements other than these include 20 wt % or less of Ag and 2 wt % or less of carbon.

[0054] The above-described bonded body is suitable for use in a circuit board. In addition, by mounting a semiconductor element on the circuit board according to the embodiment, it can also be used in a semiconductor device.

[0055] Figure 3 This is a schematic diagram showing an example of a circuit board. Figure 4 is a schematic diagram showing an example of a semiconductor device. Figure 3 and Figure 4 In the figure, 8 is a copper circuit portion, 9 is a heat sink, 10 is a semiconductor element, 11 is a lead frame, 20 is a circuit substrate, and 30 is a semiconductor device.

[0056] exist Figure 3 In the circuit board 20 shown, the copper plate 3 on the front side of the assembly 1 is processed into a copper circuit portion 8, and the copper plate 3 on the back side is processed into a heat sink 9. The circuit board 20 is produced by giving the copper plate 3 of the assembly 1 a circuit shape. Figure 4 In the semiconductor device 30 shown in FIG. 1 , a semiconductor element 10 is mounted on a copper circuit portion 8 of a circuit substrate 20. In the semiconductor device 30, in addition to the semiconductor element 10, a lead frame 11 and the like may be mounted as required. Figure 3 In the example shown, the circuit substrate 20 has a structure with two copper circuit parts 8, but the structure of the circuit substrate 20 is not limited to this example. The number and size of the copper circuit parts 8 can be changed as needed. The number of semiconductor elements 10 and lead frames 11 can also be changed arbitrarily. In addition, Figure 3 In the embodiment, the copper plate 3 on the back side is used as the heat sink 9, but the copper plates 3 on both sides may be provided with circuit structures respectively.

[0057] The side surfaces of the copper circuit portion 8 and the side surfaces of the heat sink 9 may be given an inclined shape as required. Protrusions protruding from the side ends of the copper circuit portion 8 and the side ends of the heat sink 9 may be provided on the bonding layer 4 as required. In giving the circuit structure and giving the inclined shape to the side surfaces of the copper plate, an etching process is preferably used.

[0058] Next, the manufacturing method of the bonded body according to the embodiment will be described. As long as the bonded body according to the embodiment has the above-mentioned structure, the manufacturing method thereof is not limited. Here, an example of a method for obtaining the bonded body according to the embodiment with a high yield is given.

[0059] First, a ceramic substrate 2 is prepared. Examples of the ceramic substrate 2 include a silicon nitride substrate, an aluminum nitride substrate, an aluminum oxide substrate, and an alusil substrate. The alusil substrate is a substrate in which aluminum oxide and zirconium oxide are mixed.

[0060] The copper plate 3 may be an oxygen-free copper plate or a copper alloy plate. The copper plate is preferably oxygen-free copper. As shown in JIS-H-3100 (ISO1337, etc.), oxygen-free copper is a copper plate having a copper purity of 99.96 wt% or more.

[0061] Next, a bonding brazing material is prepared, which preferably contains 50% by mass or more of Cu, 4% by mass or more and 30% by mass or less of Ti, 5% by mass or more and 40% by mass or less of one or two selected from Sn and In, 0% by mass or more and 20% by mass or less of Ag, and 0% by mass or more and 2% by mass or less of carbon.

[0062] Furthermore, as the joining brazing material, a brazing material that enables joining even in a rapid heating step at a temperature increase rate of 20° C. / min or more is prepared.

[0063] The bonding brazing material preferably has an endothermic peak in a range of 520° C. or higher and 590° C. or lower in a DSC curve based on a heating step at a heating rate of 20° C. / min.

[0064] The DSC curve can be obtained by applying heat to the sample and measuring the presence or absence of endothermic reaction and exothermic reaction by using a differential scanning calorimeter (DSC). If an endothermic reaction or an exothermic reaction occurs, a peak is generated in the DSC curve. The peak in the negative direction is an endothermic reaction, and the peak in the positive direction is an exothermic reaction. An endothermic reaction indicates that melting, decomposition, etc. of the sample occurs. An exothermic reaction indicates that a compound (including alloying) is formed or solidified by the mutual reaction of the constituent elements of the sample. It is known that the larger the peak, the greater the heat of reaction. Here, the peak in the negative direction is called an endothermic peak, and the peak in the positive direction is called an exothermic peak. In addition, the top of the peak is called a peak top. In addition, the difference between the maximum point and the minimum point of the peak is called a peak height.

[0065] For example, since the endothermic peak is in the negative direction, it rises, falls, and then rises again. The endothermic peak includes the change from maximum point → minimum point → maximum point. The minimum point (the most descending point) is the peak top. Among the maximum points on the low temperature side and the high temperature side of the minimum point, the one with the larger value (the peak with a larger value in the positive direction) is the maximum point. The peak height is the value obtained by subtracting the minimum point from the maximum point.

[0066] For example, since the exothermic peak is in the positive direction, it drops, rises, and then keeps dropping. The exothermic peak includes the change from minimum point → maximum point → minimum point. The maximum point (the highest point) is the peak top. Among the minimum points on the low temperature side and the high temperature side of the maximum point, the one with the smaller value (the peak with a larger value in the negative direction) is the minimum point. The peak height is the value obtained by subtracting the minimum point from the maximum point.

[0067] In addition, the end point of an endothermic peak (negative peak) may be regarded as an exothermic peak (positive peak), but it is calculated as an exothermic peak here. In addition, by drawing a baseline, each peak can also be obtained.

[0068] As DSC, a TGA-DSC simultaneous thermal analysis device STA449-F3-Jupiter manufactured by NETZSCH or a device having equivalent performance thereto can be used. In addition, the measurement is carried out by dropping an appropriate amount of solder into an alumina container in an Ar (argon) gas flow. The measurement is performed by covering the alumina container with a lid. Since the measurement is performed in an Ar atmosphere, it is necessary to prevent the solder from reacting with the atmosphere. Furthermore, the amount (mg) dropped is measured with a balance. In addition, the sample is specified to be 15 mg or more in terms of solid content.

[0069] The temperature profile of the DSC curve is composed of the above-mentioned heating process, holding process, and cooling process. The heating process is a process of heating from room temperature to 950°C at a heating rate of 20°C / min. The holding process is a process of holding at 950°C for 20 minutes. The cooling process is a process of cooling from 950°C to room temperature at a cooling rate of 20°C / min. The holding process is performed after the heating process, and the cooling process is performed after the holding process. In the following, the DSC curve based on the heating process with a heating rate of 20°C / min is sometimes referred to as the DSC curve of the heating process. The DSC curve based on the cooling process with a cooling rate of 20°C / min is sometimes referred to as the DSC curve of the cooling process. On the DSC curve, a difference of 0.02mW / mg or more in heat flow between the baseline and the vertex of the protrusion is calculated as a peak.

[0070] Figure 5 The DSC curve (500 to 600° C.) of the temperature increase step of the bonding brazing material used in Example 1 is shown. Figure 6 The DSC curve (700 to 900°C) of the temperature increase process of the bonding brazing material used in Example 1 is shown. Figure 5 and Figure 6 In the figure, the horizontal axis is temperature (°C) and the vertical axis is heat flow (mW / mg). Figure 5 and Figure 6 In the DSC, the heat flow is reported.

[0071] It is preferred that the DSC curve of the heating process based on the heating rate of 20°C / min has an endothermic peak in the range of 520°C to 590°C. In addition, it is preferred to have an endothermic peak in the range of 730°C to 800°C in the heating process. The endothermic peak in the range of 520°C to 590°C of the DSC curve of the heating process is referred to as the first endothermic peak. In addition, when there are two or more endothermic peaks in the range of 520°C to 590°C of the DSC curve of the heating process, the largest peak is the first endothermic peak. The so-called largest peak means a peak that is large on the negative side. In addition, the endothermic peak in the range of 730°C to 900°C of the DSC curve of the heating process is referred to as the second endothermic peak. When there are two or more endothermic peaks in the range of 730°C to 900°C of the DSC curve of the heating process, the largest peak is the second endothermic peak. The so-called largest peak means a peak that is large on the negative side. Figure 5 This is a diagram showing an example of the first endothermic peak. Figure 6 is a graph showing an example of the second endothermic peak. Figure 6 As shown, the second endothermic peak is preferably within a range of 730°C to 800°C.

[0072] The first endothermic peak indicates the decomposition reaction of TiH2. The decomposed hydrogen has the effect of removing the impurity oxygen in the brazing material and activating the metal component. The previous active metal brazing material used AgCuSnTi brazing material containing more than 40 mass% of Ag. In the previous active metal brazing material, the decomposition reaction of TiH2 occurred at 480-500°C. In other words, in the DSC curve of the previous active metal brazing material, there was no first endothermic peak. By moving the decomposition reaction of TiH2 to the high temperature side, the nitridation of the joining brazing material can be suppressed. If an active metal brazing material is used to join a nitride-based ceramic substrate and a copper plate, a Ti cohesion layer can be formed on the surface of the ceramic substrate. By moving the decomposition reaction of TiH2 to the high temperature side, it is possible to suppress the nitridation of Ti in the brazing material before reacting with the ceramic substrate. Therefore, joining in a nitrogen atmosphere can be performed.

[0073] The second endothermic peak indicates the melting reaction of Cu and the first element. Cu and the first element are elements that become the base material of the bonding brazing material. Therefore, the second endothermic peak indicates a reaction in which the bonding brazing material melts to generate a liquid phase. With respect to the conventional active metal brazing material, a decomposition reaction of TiH2 occurs at 480 to 500°C. In other words, in the conventional active metal brazing material, the first endothermic peak did not occur. By adopting a bonding brazing material that produces the first endothermic peak, the temperature difference between the peak indicating the decomposition reaction of TiH2 and the second endothermic peak indicating the melting reaction of Cu and the first element can be reduced. Thus, the bondability can be maintained even if the heating rate of the bonding process is accelerated.

[0074] It is preferred that the DSC curve of the cooling process based on a cooling rate of 20°C / min has an exothermic peak. The exothermic peak of the cooling process indicates the formation or solidification of the compound (alloy) that produces the bonding layer. The thermal stress is maximum when the molten brazing material solidifies. This is because after the bonding interface is formed, parts with different thermal expansion coefficients are constrained to each other, so stress caused by the thermal expansion difference is generated during cooling. Therefore, it is preferred that the DSC curve of the cooling process has an exothermic peak below 850°C. The DSC curve may also have two or more exothermic peaks. Having two or more exothermic peaks indicates that the compound (alloy) of the bonding layer is formed or solidified through multiple steps. Thereby, the stress relaxation effect of the joint body is improved.

[0075] In addition, it is preferred that the DSC curve of the cooling process based on a cooling rate of 20°C / min has an exothermic peak above 450°C and below 550°C. The exothermic peak above 450°C and below 550°C in the DSC curve of the cooling process based on a cooling rate of 20°C / min is called the first exothermic peak. When there are two or more exothermic peaks within this temperature range, the largest peak is taken as the first exothermic peak. If the exothermic peak of the cooling process is lower than 450°C, there is a possibility that the solidification temperature is too low and the reliability of the bonding is reduced. On the other hand, if the exothermic peak is as high as more than 550°C, there is a possibility that the thermal stress increases.

[0076] In addition, when comparing the peak top temperatures of the first endothermic peak of the heating process and the first exothermic peak of the cooling process, it is preferred that the peak top temperature of the first exothermic peak is lower. The first endothermic peak is mainly generated by the decomposition reaction of TiH2. On the other hand, the first exothermic peak of the cooling process is an exothermic reaction generated by the solidification of the bonding layer or the formation of a Ti compound. By making the temperature of the peak top position of the first exothermic peak of the cooling process lower than the temperature of the peak top position of the first endothermic peak of the heating process, the generation of thermal stress in the cooling process can be suppressed. Furthermore, as long as the cooling process has an exothermic peak, the first exothermic peak may not be present. In addition, the same effect can be obtained by having two or more exothermic peaks in the DSC curve of the cooling process.

[0077] For the above-mentioned bonding brazing materials, bonding can be performed even if the heating rate is 20°C / min or more or the cooling process is 20°C / min or more. In addition, the bonding atmosphere can also be a vacuum or a nitrogen atmosphere. The so-called vacuum is 1×10 -3 Pa or less. In addition, the nitrogen atmosphere is an atmosphere in which nitrogen is 70 vol% or more. In addition, as components other than nitrogen, argon gas or air can be mentioned.

[0078] To control the DSC curve, it is effective to control the composition of the brazing material. As the bonding brazing material, it is preferred to contain 50% by mass or more of Cu, 4% by mass or more and 30% by mass or less of Ti, 5% by mass or more and 40% by mass or less of one or two selected from Sn and In, 0% by mass or more and 20% by mass or less of Ag, and 0% by mass or more and 2% by mass or less of carbon.

[0079] The total of Cu, Ti and the first element is preferably 80% by mass or more, more preferably 90% by mass or more and 100% by mass or less. In addition, the total of Cu and the first element is preferably 70% by mass or more. In fact, by reducing the presence ratio of Ag, the melting point of the solder can be increased. Thus, even if the heating rate and the cooling rate are accelerated, a solder having a DSC curve as a target can be obtained.

[0080] The average particle size D of the Cu powder used as the brazing material is 50 Preferably, it is 12.0 μm or less, and more preferably, it is 10.0 μm or less. In addition, the average particle size D of the TiH2 powder is 50 The average particle size D of Sn powder or In powder is preferably 6.0 μm or less, and more preferably 4.0 μm or less. 50 It is preferably 16.0 μm or less, and more preferably 14.0 μm or less. The average particle size D of the C powder 50 The average particle size D of the Ag powder is preferably 6.0 μm or less, and more preferably 4.0 μm or less. 50 It is preferably 3.0 μm or less, and more preferably 2.0 μm or less. By controlling the particle size of the powder, the reaction of each powder can be made uniform.

[0081] The average particle size D of the Cu powder is preferably 50 Smaller than the average particle size D of Sn powder or In powder 50 As mentioned above, regarding the solder composition, Cu and the first element become the base material. Sn and In are elements with lower melting points than Cu. By increasing the particle size of Sn or In, the reaction between Sn powder and Cu powder or the reaction between In powder and Cu powder can be made homogenous. Thus, bonding can be performed even if the heating rate or cooling rate is increased.

[0082] In addition, the difference between the heating rate and the cooling rate is preferably less than 20°C / minute. That is, it is preferably satisfied that |heating rate-cooling rate|≤20°C / minute. By heating the brazing material layer, a melting reaction and a solidification reaction are generated. These reactions can occur in the heating process and the cooling process. By reducing the difference between the heating rate and the cooling rate, the stress generated in the reaction can be homogenized. Thus, undesirable phenomena such as warping can be suppressed. In addition, it is also effective to control the area ratio of the Ti-rich zone, the Ti-poor zone, and the Ti-medium zone.

[0083] The process of joining the ceramic substrate and the copper plate is performed by using the above-mentioned joining brazing material. The joining brazing material is mixed with an organic substance to prepare a brazing paste. The brazing paste is applied on the surface of the ceramic substrate 2 (or the copper plate 3) to form a brazing paste layer. The copper plate 3 (or the ceramic substrate 2) is arranged on the brazing paste layer.

[0084] The heat bonding process can be performed in a vacuum or a nitrogen atmosphere. -3 Pa or less. In addition, the so-called nitrogen atmosphere is an atmosphere in which nitrogen is 70 vol% or more. The nitrogen content of the nitrogen atmosphere is preferably 70 vol% or more, and more preferably 85 vol% or more and 100 vol% or less. The nitrogen atmosphere may contain argon or air in addition to nitrogen. When heat bonding is performed in a nitrogen atmosphere, it can be performed under various conditions such as normal pressure, reduced pressure, and pressurized pressure.

[0085] In the heating process of the heating joining process, the heating rate is set to be above 20°C / minute. In the previous active metal joining method, the heating rate is below 5°C / minute. By adopting a joining brazing material having a DSC curve as described above, joining can be performed even if the heating rate is increased. There is no particular limit on the upper limit of the heating rate, but it is preferably below 100°C / minute. If it is accelerated by more than 100°C / minute, there is a possibility that the bondability will decrease. Therefore, the heating rate is preferably above 20°C / minute and below 100°C / minute, and more preferably above 30°C / minute and below 70°C / minute.

[0086] The temperature is raised to the joining temperature through a heating process. The joining temperature is set at 750°C or higher. In addition, the joining temperature is set at a temperature higher than the peak temperature of the second endothermic peak. The second endothermic peak is located at 730-800°C. By setting the joining temperature at a temperature higher than the peak temperature of the second endothermic peak, the melting reaction of the solder can occur properly. Therefore, the joining temperature is preferably above 750°C, and more preferably above 800°C. Furthermore, the upper limit of the joining temperature is preferably below 1000°C. If it is as high as more than 1000°C, it is close to the melting point of copper (1085°C), and there is a possibility of deformation of the copper plate.

[0087] The bonding temperature is preferably maintained for more than 10 minutes. The time maintained at the bonding temperature is referred to as the heating holding time. The heating holding time is preferably more than 10 minutes and less than 100 minutes. If the heating holding time is less than 10 minutes, there is a possibility that the solder melts and solidifies in insufficient time. In addition, if it is longer than 100 minutes, there is a possibility that Sn or In is excessively diffused in the copper plate.

[0088] After the heating holding time is over, a cooling process is performed. The cooling process is a process of cooling from the joining temperature to room temperature. The cooling rate is set to be above 20°C / minute. In the previous active metal joining method, the cooling rate was about 5°C / minute. By adopting a joining brazing material having a DSC curve as described above, joining can be performed even if the cooling rate is increased. There is no particular limit on the upper limit of the cooling rate, but it is preferably below 100°C / minute. If it is accelerated by more than 100°C / minute, there is a possibility that the bondability will decrease. Therefore, the cooling rate is preferably above 20°C / minute and below 100°C / minute, and more preferably above 30°C / minute and below 70°C / minute.

[0089] Furthermore, the heat bonding step may be performed while adding weight to the bonded body 1 as necessary.

[0090] Through the above-mentioned bonding process, the bonded body 1 can be manufactured. By accelerating the heating rate of the heating process and the cooling rate of the cooling process, the heat applied to the bonded body 1 can be reduced. As a result, the distribution of Ti and the first element in the bonding layer can be controlled. In addition, the diffusion amount of Sn (or In) into the copper plate can also be reduced.

[0091] Since the amount of heat applied to the bonded structure 1 can be reduced, the warping of the bonded structure 1 and the deformation of the copper plate 3 can also be reduced.

[0092] The obtained joint body 1 is subjected to etching processing to be processed into a circuit substrate 20. In addition, multiple simultaneous processing can also be performed as needed. The so-called multiple simultaneous processing is a method of obtaining a small joint body by cutting a large joint body. There is also a method of splitting a joint body or a method of splitting a ceramic copper circuit substrate. In order to facilitate the splitting, a scribing process can also be performed.

[0093] * Instructions for appropriating past applications.

[0094] (Example)

[0095] (Examples 1 to 5, Comparative Example 1, Reference Examples 1 to 2)

[0096] The bonding brazing materials shown in Tables 1 and 2 were prepared. Table 1 shows the particle size of the raw material powder. Table 2 shows the composition ratio.

[0097] Table 1

[0098]

[0099] Table 2

[0100]

[0101] The bonding brazing materials components according to the examples and comparative examples were mixed with an organic binder to prepare brazing pastes. A DSC curve was measured using DSC for each brazing paste.

[0102] As DSC, a TGA-DSC simultaneous thermal analysis device STA449-F3-Jupiter manufactured by NETZSCH was used. In addition, an appropriate amount of brazing material was dropped on the alumina container and measured in an Ar gas flow. The alumina container was covered and measured. The temperature program was set to a heating rate of 20°C / min, 950°C×20 minutes, and a cooling rate of 20°C / min. A sample of 15 mg in terms of solid content was used.

[0103] The presence or absence of the first endothermic peak and the second endothermic peak in the temperature increase step was investigated. In addition, the peak top temperature was investigated. The results are shown in Table 3.

[0104] Table 3

[0105]

[0106] As can be seen from the table, the first endothermic peak and the second endothermic peak were observed in the bonding brazing material according to the example. In contrast, in Comparative Example 1, the endothermic peak indicating the decomposition reaction of TiH2 was lower than 520°C. In other words, the first endothermic peak was not observed.

[0107] Next, a silicon nitride substrate was prepared as a ceramic substrate. A silicon nitride substrate with a thermal conductivity of 90 W / m·K, a three-point bending strength of 600 MPa, and a length of 50 mm × a width of 40 mm × a thickness of 0.32 mm was used. As a copper plate, an oxygen-free copper plate with a length of 50 mm × a width of 40 mm × a thickness of 0.5 mm was prepared. A 30 μm brazing paste was applied to both sides of the ceramic substrate, and a copper plate was placed thereon.

[0108] Next, a heat bonding step was performed. The bonding atmosphere was uniformly a nitrogen atmosphere. In addition, the bonding conditions were uniformly 850° C.×20 minutes. The heating rate and the cooling rate were set to the conditions shown in Table 4.

[0109] Table 4

[0110]

[0111] The bonded bodies were manufactured by the above steps. Ten bonded bodies were manufactured for each of the examples and the comparative examples.

[0112] Next, observe the cross-sectional structure of the obtained joint. Observe the cross section of the joint by SEM-EDX. Observe the measurement area of ​​20μm×10μm in the joint layer, and observe the Ti-rich area and the Ti-poor area. Regarding the cross-sectional structure, observe any three places that do not overlap with each other. Regarding the presence or absence of Ti-rich areas and Ti-poor areas, those observed in all three places are set to "yes", and those not observed in even one place are set to "no". In addition, as an area ratio, record the lower limit and upper limit of the measurement results. In addition, regarding the mass ratio of Cu and Sn, calculate the average value of the ratio of the mass of Cu to the mass of Sn.

[0113] Observe the diffusion area of ​​Sn to the copper plate. Ti Mass M relative to Sn Sn The ratio (M Ti / M Sn ) is greater than 0.5 as the Ti-rich region. Ti / M Sn ) is below 0.1 as the Ti-poor area.

[0114] When the bonding layer 2 is divided from the center, the mass ratio (M Ti / M Sn ) is greater than the mass ratio (M Ti / M Sn In addition, when the cross section of the bonding layer is analyzed, the mass ratio (M Ti / M Sn ) is less than 1.

[0115] Furthermore, as the diffusion region of Sn into the copper plate, the position where 1 mass % or more of Sn was observed in the copper plate was determined.

[0116] Table 5

[0117]

[0118] Table 6

[0119]

[0120] As shown in the table, in the bonded body of the embodiment, Ti-rich region and Ti-poor region are observed in the bonded layer. Ti / M Sn ) is within the range of 0.5 or more and 1.2 or less. In addition, one or two intermetallic compounds of Sn3Ti5 and Sn5Ti6 are detected in the Ti-rich region and the Ti-poor region.

[0121] When the bonding layer is observed using a SEM reflected electron image, the area that appears whitish at high contrast in the reflected electron image is roughly consistent with the Ti-rich region identified from the SEM-EDX analysis results. Regarding the area ratio of the Ti-rich region, it is found that the method of investigating using SEM reflected electron images is effective.

[0122] The height of the diffusion region of Sn into the copper plate is also less than 100 μm, and further less than 50 μm. It is known that any solder having a DSC curve with a predetermined peak when the heating rate and the cooling rate are 20°C / min has the effect of inhibiting the diffusion of Sn into the copper plate.

[0123] In contrast, in the comparative example, no Ti-rich region was observed. Therefore, the height of the region where Sn diffused into the copper plate exceeded 100 μm.

[0124] Next, the warping amount of the obtained joint body and the bonding strength of the copper plate are measured. Regarding the warping amount, the warping amount on the long side is measured. The ones with all 10 warping amounts of less than 0.3 mm are regarded as the best products (◎). In addition, the ones with 1 to 3 warping amounts exceeding 0.3 mm are regarded as good products (○). The ones with 4 or more warping amounts exceeding 0.3 mm are regarded as defective products (×). In addition, the bonding strength of the copper plate is regarded as the peel strength. Specifically, in each embodiment and comparative example, a sample for peeling test is prepared. The sample is a long copper plate bonded to a ceramic substrate. At this time, the bonding is performed in a manner that one end of the copper plate protrudes from the ceramic substrate. The peel strength is measured by vertically stretching the protruding copper plate. The results are shown in Table 7.

[0125] In addition, an example in which the heating rate and the cooling rate of Example 1 were set to 5° C. / min was referred to as Reference Example 1. An example in which the heating rate and the cooling rate of Comparative Example 1 were set to 5° C. / min was referred to as Reference Example 2.

[0126] Table 7

[0127] Warpage Bonding strength (kN / mm) Example 1 ◎ 15 Example 2 ◎ 17 Example 3 ◎ 19 Example 4 ◎ 15 Example 5 ○ 15 Comparative Example 1 × 13 Reference Example 1 ◎ 6 Reference Example 2 × 3

[0128] As can be seen from the table, the warpage amount and bonding strength of the bonded body involved in the embodiment are also excellent. Correspondingly, since the amount of Ag is large in Comparative Example 1, if the heating rate and the cooling rate are fast, it is not possible to properly bond. In addition, as in Example 5, when the difference between the heating rate and the cooling rate exceeds 20°C / min, it is found that the warpage amount is deteriorated. Therefore, it is known that the difference between the heating rate and the cooling rate is preferably less than 20°C / min.

[0129] In addition, the warpage amount of Reference Example 1 is small, but the bonding strength is reduced. It is known that the bonding brazing material of the embodiment is suitable for a fast bonding process with a heating rate of 20°C / min or more. In addition, the same is true in Reference Example 2. In a nitrogen atmosphere, nitridation progresses in a bonding brazing material containing more Ag, and the bonding strength is reduced.

[0130] From the above, it can be seen that as long as the solder has a DSC curve with a predetermined peak when the heating rate and the cooling rate are 20°C / min, even if the heating rate and the cooling rate of the bonding process are accelerated to 20°C / min or more, excellent bonding can be obtained. Therefore, it is known that the bonded body involved in the embodiment has a small warpage and excellent mass production.

[0131] Several embodiments of the present invention are illustrated above, but these embodiments are presented as examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other ways, and various omissions, substitutions, changes, etc. can be made without departing from the scope of the main purpose of the invention. These embodiments and their modifications are included in the scope and main purpose of the invention, and are also included in the invention described in the claims and their equivalents. In addition, the above-mentioned embodiments can be implemented in a combination with each other.

[0132] Explanation of symbols

[0133] 1-joint, 2-ceramic substrate, 3-copper plate, 4-joining layer, 5-Ti-rich region, 6-Ti-poor region, 7-diffusion region, 8-copper circuit portion, 9-copper heat sink, 10-semiconductor element, 11-lead frame, 20-circuit substrate, 30-semiconductor device.

Claims

1. A circuit substrate, characterized in that: It has: Ceramic substrate, Copper plate, and a bonding layer disposed on at least one side of the ceramic substrate and used for bonding the ceramic substrate and the copper plate; The bonding layer contains Cu, Ti and the first element Sn; The bonding layer includes a Ti agglomerate layer formed on the surface of the ceramic substrate, a Ti mass M Ti Relative to the mass M of the first element E1 Ratio M Ti / M E1 The Ti-rich region is 0.5 or more and the ratio M Ti / M E1 Poor Ti area with a value below 0.1; When the cross section of the bonding layer is analyzed, the ratio M Ti / M E1 Less than 1; When the bonding layer is divided into two equal parts, the ratio M in the area on the ceramic substrate side is Ti / M E1 greater than the ratio M in the area on the copper plate side Ti / M E1 ; The Ti-rich region and the Ti-poor region are located between the Ti agglomerate layer and the copper plate.

2. The circuit substrate according to claim 1, characterized in that: The ratio M in the Ti-rich region Ti / M E1 It is 0.5 or more and 1.2 or less.

3. The circuit substrate according to claim 1 or 2, characterized in that: In the Ti-rich region, the mass of Cu M Cu Relative to mass M E1 Ratio M Cu / M E1 It is 0.05 or more and 0.4 or less.

4. The circuit substrate according to claim 1 or 2, characterized in that: In the Ti-depleted region, the mass of Cu M Cu Relative to mass M E1 Ratio M Cu / M E1 It is 3 or more and 10 or less.

5. The circuit substrate according to claim 3, characterized in that: In the Ti-depleted region, the mass of Cu M Cu Relative to mass M E1 Ratio M Cu / M E1 It is 3 or more and 10 or less.

6. The circuit substrate according to claim 1 or 2, characterized in that: The copper plate includes a diffusion region in which the diffusion amount of the first element from the interface between the bonding layer and the copper plate is 1 wt % or more, The length of the diffusion region in a direction connecting the ceramic substrate and the copper plate is 100 μm or less.

7. The circuit substrate according to claim 5, characterized in that: The copper plate includes a diffusion region in which the diffusion amount of the first element from the interface between the bonding layer and the copper plate is 1 wt % or more, The length of the diffusion region in a direction connecting the ceramic substrate and the copper plate is 100 μm or less.

8. The circuit substrate according to claim 1 or 2, characterized in that: The copper plate includes a diffusion region in which the diffusion amount of the first element from the interface between the bonding layer and the copper plate is 1 wt % or more, The length of the diffusion region in a direction connecting the ceramic substrate and the copper plate is 50 μm or less.

9. The circuit substrate according to claim 1 or 2, characterized in that: The copper plate has a thickness of 0.3 mm or more.

10. The circuit substrate according to claim 7, characterized in that: The copper plate has a thickness of 0.3 mm or more.

11. A semiconductor device, characterized in that: It has: The circuit substrate according to any one of claims 1 to 10, and A semiconductor element is mounted on the circuit substrate.

Citation Information

Patent Citations

  • Assembly and power-module substrate

    CN105393347A

  • Substrate for power modules

    CN109155291A

  • Bonded substrate and method for manufacturing bonded substrate

    US20170323842A1